2021
DOI: 10.1302/2046-3758.101.bjr-2020-0229.r1
|View full text |Cite
|
Sign up to set email alerts
|

Radiological and clinical outcomes using induced membrane technique combined with bone marrow concentrate in the treatment of chronic osteomyelitis of immature patients

Abstract: Aims Treatment of chronic osteomyelitis (COM) for young patients remains a challenge. Large bone deficiencies secondary to COM can be treated using induced membrane technique (IMT). However, it is unclear which type of bone graft is optimal. The goal of the study was to determine the clinical effectiveness of bone marrow concentrator modified allograft (BMCA) versus bone marrow aspirate mixed allograft (BMAA) for children with COM of long bones. Methods Between January 2013 and December 2017, 26 young patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 35 publications
(20 reference statements)
0
14
0
Order By: Relevance
“…Establishing the best surgical option in treating musculoskeletal neoplastic and non-neoplastic conditions is ongoing. [17][18][19][20][21][22][23] Our comparison of rAPC reconstruction with osteoarticular allograft reconstruction in treating distal femoral tumours in children revealed knee stability and functional outcomes were statistically significantly better in the rAPC group, while the ROM in the knee was statistically significantly better in the osteoarticular allograft group. These findings were clinically relevant.…”
Section: Discussionmentioning
confidence: 76%
“…Establishing the best surgical option in treating musculoskeletal neoplastic and non-neoplastic conditions is ongoing. [17][18][19][20][21][22][23] Our comparison of rAPC reconstruction with osteoarticular allograft reconstruction in treating distal femoral tumours in children revealed knee stability and functional outcomes were statistically significantly better in the rAPC group, while the ROM in the knee was statistically significantly better in the osteoarticular allograft group. These findings were clinically relevant.…”
Section: Discussionmentioning
confidence: 76%
“…Some studies reported the volume of bone defects rather than their length. 21,36,58 Study and patient characteristics are summarized in Table I. Surgical parameters.…”
Section: Resultsmentioning
confidence: 99%
“…77 However, our multivariate analysis did not reach that conclusion, which is significantly different from the clinical effects reported in previous studies. 58,78 Masquelet even believed that adding BMP-7 leads to a poor prognosis of infected bone defects. 3 Age is a recognized factor affecting bone healing.…”
Section: Discussionmentioning
confidence: 99%
“…Their results showed that BTP was even more effective in osteogenesis than bone graft. Shen et al [ 30 ] used bone marrow concentrator–modified allograft or bone marrow aspirate–mixed allograft to improve the osteogenic ability of allograft. In this study, allograft bone was added as an alternative graft material to increase the graft volume.…”
Section: Discussionmentioning
confidence: 99%